IMPLEMENTASI PROBLEM BASED LEARNING DENGAN STRATEGI READING GUIDE UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA - SUHENDRA, AHMAD; KURNIAWAN, ARIS (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
This study aims to obtain information on the improvement of conceptual understanding and the students' cognitive learning outcomes completeness through the application of Problem-Based Learning (PBL) with a reading guide strategy in the elasticity material at SMAN 2 Sumber Barito. This study uses a descriptive method. The instruments used include a conceptual understanding test administered at the beginning and end of each meeting, as well as a cognitive learning outcome test administered at the end of all meetings. The research sample consists of 42 students from class XI IPA. The results reveal that students' conceptual understanding of the elasticity material experienced a significant improvement, with an overall N-Gain score percentage of 61% in the medium category. The students' cognitive learning outcomes completeness classically reached 80.95%, with 34 students achieving individual learning completeness. ABSTRAKPenelitian ini bertujuan untuk memperoleh informasi mengenai peningkatan pemahaman konsep dan ketuntasan hasil belajar kognitif siswa melalui penerapan Problem Based Learning dengan strategi reading guide di SMAN 2 Sumber Barito pada materi elastisitas. Penelitian ini menggunakan metode deskriptif. Instrumen yang digunakan meliputi tes pemahaman konsep yang diujikan pada awal dan akhir setiap pertemuan, serta tes hasil belajar kognitif yang diujikan pada akhir seluruh pertemuan. Sampel penelitian ini sebanyak 42 siswa kelas XI IPA. Hasil penelitian mengungkapkan bahwa pemahaman konsep siswa pada materi elastisitas mengalami peningkatan yang signifikan, dengan persentase skor N-Gain sebesar 61% dalam kategori sedang. Ketuntasan hasil belajar kognitif siswa secara klasikal mencapai 80.95%, dengan 34 siswa mencapai ketuntasan belajar secara individu.